2013
DOI: 10.1007/s12928-013-0226-4
|View full text |Cite
|
Sign up to set email alerts
|

A case of delayed complete atrioventricular block and cardiac arrest after percutaneous coronary intervention of left anterior descending coronary artery

Abstract: Delayed complete atrioventricular (AV) block due to jailed septal branch during percutaneous coronary intervention (PCI) of left anterior descending artery is a rare complication. Here, we present a case of an elderly male who developed episodes of complete AV block and cardiac arrest 2 days after transient occlusion of the septal branch during PCI, and received permanent pacemaker implantation. This case had shown first-degree AV block plus right bundle branch block before PCI, and the presence of these preex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…We reviewed the English literature and found only eight published case reports on delayed complete AV block following "jailed"/occluded SPB of LAD (Table). [2][3][4][5][6][7][8][9] The occlusion of SPB can lead to angina, myocardial infarction, and conduction abnormalities. Various mechanisms have been proposed, including plaque shift, the snow-plow effect, and stent jailing of the side branch.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We reviewed the English literature and found only eight published case reports on delayed complete AV block following "jailed"/occluded SPB of LAD (Table). [2][3][4][5][6][7][8][9] The occlusion of SPB can lead to angina, myocardial infarction, and conduction abnormalities. Various mechanisms have been proposed, including plaque shift, the snow-plow effect, and stent jailing of the side branch.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the eight published cases demonstrated the following various conduction abnormalities at baseline: first-degree AV block, left bundle branch block, CRBBB, and LAFB. [2][3][4][5][6][7][8][9] To treat hypertrophic obstructive cardiomyopathy, a procedure known as "percutaneous transluminal septal myocardial ablation (PTSMA)," which results in SPB occlusion, can be used. Chang, et al concluded that left bundle branch block (odds ratio: 39; P = 0.002) and first-degree AV block (odds ratio: 14; P = 0.001) on base-line ECG are independent predictors of complete AV block after PTSMA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports have predominantly described third-degree AVB in the setting of inferior MI or even severe RCA stenosis without MI 4 . Cases of third-degree AVB secondary to anterior MI have also been described, albeit with different prognoses 5 , 6 . Additionally, there have been reports concerning the occurrence of third-degree AVB due to septal occlusion (i.e.…”
Section: Discussionmentioning
confidence: 99%